Vertical Scar Mammaplasty - Hamdi, Moustapha; Hammond, Dennis C.; Nahai, Foad (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Over the past decade vertical scar mammaplasty has gained wide popularity amongst surgeons and patients because it stands for minimal scars and long-lasting aesthetic results. The refinements and modifications of the technique achieved during the past decade and now collected in this book will facilitate the use of the technique and give each plastic surgeon the opportunity to adopt his or her own technique to obtain an optimal outcome. The step-by-step instructions and their high-quality illustrations will help improve results, lessen the number of complications and successfully manage any complications that do arise.